2023
DOI: 10.3390/ani13081365
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Sexual Correlates of Gut Microbiota in the Japanese Gecko, Gekko japonicus (Schlegel, 1836)

Abstract: Numerous studies have demonstrated that multiple intrinsic and extrinsic factors shape the structure and composition of gut microbiota in a host. The disorder of the gut microbiota may trigger various host diseases. Here, we collected fecal samples from wild-caught Japanese geckos (Gekko japonicus) and captive conspecifics fed with mealworms (mealworm-fed geckos) and fruit flies (fly-fed geckos), aiming to examine the dietary and sexual correlates of the gut microbiota. We used 16S rRNA gene sequencing technol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 81 publications
0
2
2
Order By: Relevance
“…Our study showed that the phyla Bacteroidota, Firmicutes, and Proteobacteria accounted for more than 97% of the gut microbiome, indicating that these bacterial phyla were the predominant ones in P. gerrhopygus . In contrast to our results, the top four dominant bacterial phyla in the Japanese gecko ( Gekko japonicus ) and leopard gecko ( Eublepharis macularius ) were Verrucomicrobiota, Bacteroidota, Firmicutes, and Proteobacteria [ 11 , 57 ]. It was recently reported that Proteobacteria, Firmicutes, Bacteroidota, and Actinobacteria were the dominant phyla of the gut microbiome of the Tokay gecko ( Gekko gecko ) [ 62 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our study showed that the phyla Bacteroidota, Firmicutes, and Proteobacteria accounted for more than 97% of the gut microbiome, indicating that these bacterial phyla were the predominant ones in P. gerrhopygus . In contrast to our results, the top four dominant bacterial phyla in the Japanese gecko ( Gekko japonicus ) and leopard gecko ( Eublepharis macularius ) were Verrucomicrobiota, Bacteroidota, Firmicutes, and Proteobacteria [ 11 , 57 ]. It was recently reported that Proteobacteria, Firmicutes, Bacteroidota, and Actinobacteria were the dominant phyla of the gut microbiome of the Tokay gecko ( Gekko gecko ) [ 62 ].…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, Arizza et al (2019) found that the dominant bacterial families in the gut microbiome of sea turtles ( Caretta caretta ) included Ruminococcaceae, Rikenellaceae, Lachnospiraceae, and Clostridiales [ 66 ]. However, our results differed from those reported for other geckos, such as the wild-caught Japanese gecko ( G. japonicas ), where the dominant bacterial families were Akkermansiaceae, Bacteroidaceae, Tannerellaceae, Enterobacteriaceae, Lachnospiraceae, and Clostridiaceae [ 57 ]. These discrepancies are likely due to differences in the species, the environmental conditions, and the sampling methods.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations